SAMA: Self-adjusting multi-cycle approximate adder. (April 2023) - Baratalipour, Elahe; Kamran, Arezoo
Abstract: Approximate computing is a promising approach that leads to a better compromise between power and delay by trading an acceptable level of accuracy in inherently error resilient applications. In this paper, we present a runtime accuracy configurable approximate adder that can operate in both approximate and exact modes. It provides a better compromise between power, delay, and accuracy compared with state-of-the-art approximate adders at high accuracies. Our evaluations show that the proposed adder can make up to 45% and 79% improvements in power-delay product (PDP) and energy-delay product (EDP), respectively, compared with state-of-the-art approximate adders, at high accuracies. In the accurate mode, the improvements in the PDP and EDP are up to 58% and 82%, respectively. The use of the proposed adder in an image processing application and in a mean-squares prediction algorithm confirms its superiority over existing circuits in terms of PDP and EDP.